FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Fadlillah, Muhammad Rizali (Politeknik Negeri Madiun, 2019)
This study conducted to understand and get empirical evidence from the effect of factors which represented by Liquidity, Leverage, Operating Capacity, Profitability and Firm Growth on Financial Distress at manufacture companies which listed on Indonesia Stock Exchange from 2015-2017. This study is an associative research category. This study uses quantitative methods to determine the effect of a variable on other variables. All of manufacturing companies which listed on the Indonesia Stock Exchange in the period 2015 to 2017 are the population of this study. Then, the number of samples used are 101 companies which purposive sampling as the sample technique. Samples are selected using the specified criteria.The factors that become the variables in this research are liquidity, leverage, operating capacity, profitability and firm growth as independent variables, and financial distress as dependent variable. This research used secondary data. The data analysis technique used binary logistic regression supported by SPSS version 23. The result of this research showed that liquidity, leverage, operating capacity, and profitability have significant influence on the condition of financial distress of manufacturing companies listed in Indonesia Stock Exchange. Meanwhile, firm growth do not have significant influence on the condition of financial distress of manufacturing companies listed in Indonesia Stock Exchange.